Impact of Feeding Programs on Students’ Learning in Government Aided Secondary Schools in Kapyanga Sub County, Bugiru District - Hussein Balikowa (Uganda Christian University, 2024)
The research was guided by the topic impact of feeding programs on students learning in Government aided secondary schools in Kapyanga Sub County Bugiri District. The study was guided by the following research objectives: to assess the various forms of feeding programs in government aided secondary schools in Kapyanga Sub-County Bugiri district, to ascertain the relationship between feeding programs and students learning in government secondary schools in Kapyanga sub-county Bugiri District, to examine strategies for improving feeding programs and enhance student’s learning in government secondary schools in Kapyanga sub-county Bugiri District. The study used both a quantative and qualitative research design and it considered a sample size of 131 respondents. Study findings revealed that: there are a number of feeding programs in schools in Kapyanga Sub County, findings indicated that school feeding programs for attendance and enrollment lead to increase in enrollment, findings indicated that school feeding program is a developmental intervention that aids recovery that works as a form of feeding. Findings revealed that there is a relationship between school feeding programs and students learning, that absenteeism’s in schools is as a result of no school feeding programs which makes students to absentee themselves, findings indicated that building of consensus policy objectives that focus on feeding may contribute to improving education. Findings concluded that there are a number of feeding programs in schools in Kapyanga Sub County, findings also concluded that school feeding program is an intervention to combat food shortages. The study recommended that: There should be more policies designed by the Government to ensure students have meals in schools to ensure better performance, that there is need for schools to design better feeding programs that can help students in order to ensure better performance and lastly that parents should always support school feeding programs such that their children can benefit.